(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Native of the moderate and mountainous parts of the Western Himalaya, Angelica glauca Edgew., also referred to as Choraka, of Himalayas Angelica, is a valuable medicinal and fragrant plant. The species is well-known in traditional medical systems for its therapeutic qualities and is used to treat inflammatory, pulmonary, and digestive diseases. A. glauca’s sturdy permanent habit, hollowed aromatic stems, broad veined blades, and interconnected umbels are among its botanical characteristics that help explain its ecological resilience in high-altitude settings. Despite its significance, the species’ natural populations have rapidly declined due to unchecked mining, degraded habitat, and climate change, placing it under vulnerable status. The taxonomic classification, morphology, phytochemical composition, along with traditional medicinal use of Angelica glauca are highlighted in this overview of the plant’s botanical significance. It also looks at modern conservation tactics, including as cultivation methods, tissue culture techniques, in situ and ex situ methodologies, along with regulatory-driven sustainable harvesting frameworks. One important strategy for guaranteeing the long-term survival of species is the integration of traditional knowledge with contemporary scientific solutions. The study emphasises the critical need for interdisciplinary conservation initiatives to safeguard A. glauca and encourage its sustainable use for coming generations.